Statics -- formulas and problems. - Gross, D. (Springer, 2017)
This book contains the most important formulas and more than 160 completely solved problems from Statics. It provides engineering students material to improve their skills and helps to gain experience in solving engineering problems. Particular emphasis is placed on finding the solution path and formulating the basic equations. Topics include: - Equilibrium - Center of Gravity, Center of Mass, Centroids - Support Reactions - Trusses - Beams, Frames, Arches - Cables - Work and Potential Energy - Static and Kinetic Friction - Moments of Inertia.